Analisis Strategi Representasi Diri dan Personal Branding pada Beauty Content Creator di Instagram Reels - Rifayani, Tsanaara Qinthara; Harahap, Junardi (Department of Anthropology, 2025)
The rise of short-form video platforms, specifically Instagram Reels, has transformed social media into a crucial, highly strategic stage for individuals to perform and negotiate their identities. This study critically analyzes the self-representation and personal branding strategies employed by Fani Rahmawati, a beauty content creator, on Instagram Reels to build a public image that is both credible and emotionally relatable. Utilizing a descriptive qualitative approach and virtual ethnography, the research delves into the subtle symbolic, social, and performative dynamics inherent in digital identity construction. Data collection relied on participative observation of Fani's Reels content (March–April 2024) and in-depth interviews with the creator, her videographer, and an active follower. Trustworthiness was ensured through source triangulation and member-checking. Thematic analysis, informed by Goffman's impression management and Jones and Pittman's strategic self-presentation, revealed five interconnected themes: visual consistency, an intimate communication style, constructed authenticity, emotional audience engagement, and the significant role of the production team. The findings indicate that Fani successfully fosters a